2000
DOI: 10.1093/jnci/92.24.1979
|View full text |Cite
|
Sign up to set email alerts
|

Hutchinson Smoking Prevention Project: Long-Term Randomized Trial in School-Based Tobacco Use Prevention--Results on Smoking

Abstract: The rigor of the HSPP trial suggests high credence for the intervention impact results. Consistent with previous trials, there is no evidence from this trial that a school-based social-influences approach is effective in the long-term deterrence of smoking among youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
187
0
15

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(205 citation statements)
references
References 67 publications
3
187
0
15
Order By: Relevance
“…This study used data from the landmark Hutchinson Smoking Prevention Project (HSPP)-a 15-year, 40 school district schoolbased tobacco use prevention randomized trial (Peterson, Kealey, Mann, Marek, & Sarason, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used data from the landmark Hutchinson Smoking Prevention Project (HSPP)-a 15-year, 40 school district schoolbased tobacco use prevention randomized trial (Peterson, Kealey, Mann, Marek, & Sarason, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, all models accounted for intraclass correlations due to clustering within a school district by using Stata's cluster variance estimation option. Per HSPP trial design specifications, all 40 districts had one HS per district (Peterson et al, 2000). Therefore, clustering by school district was analytically the same as that by HS.…”
Section: Covariatesmentioning
confidence: 99%
“…Estimates of cancer mortality for the year 2000 for all 10 accession countries were derived from the Globocan 2000 software and database. 13 Age-standardized mortality rates (ASRs) were calculated for all ages combined and for age groups [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] Hungary and Poland) and for age groups 20 -44, 45-64 and 65 and over (Estonia, Latvia, Lithuania, Slovakia and Slovenia) for each sex separately. The World Standard Population was used for age adjustment.…”
mentioning
confidence: 99%
“…But as noted by Joule et al (2008), "good ideas" do not automatically lead to "proper behavior". They illustrate the gap between good ideas and proper behavior with a study on smoking prevention; Peterson et al (2000) found no difference in behavior between students 8-17 years old who were part of preventive sessions in class and the control group. Persuasive communication is necessary but not sufficient, because it changes minds but poorly acts on actions.…”
Section: Cheap Talkmentioning
confidence: 95%